Research on obstacle avoidance for aerial work vehicle booms with light arrays based on an improved gradient projection method - Yi HUANG; Lei DENG; Kangyi DENG; Qin SHU; Guangan REN; Zhihong ZHOU (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2025)
In order to solve the spatial obstacle avoidance requirements of the boom jitter caused by the gradient projection method control in the self-motion of the hybrid light array high-altitude vehicle, which leads to the discontinuous motion trajectory and the multi-obstacle environment, this paper proposes a boom obstacle avoidance control method based on the improved gradient projection method. In order to suppress the jib jitter, a boom motion stability control algorithm was designed, and the improved gradient projection method was divided into two parts, which were controlled separately according to the proportion of the length of the telescoping arm to achieve stable movement. In terms of obstacle avoidance, the obstacle is modeled by the hyperquadric surface function, and the proximity between the boom and the obstacle is evaluated by using the pseudo-distance instead of the Euclidean distance, and the obstacle avoidance escape speed is introduced on this basis to effectively avoid collision. At the same time, the end position error reduction algorithm is added to reduce the end velocity and improve the trajectory tracking accuracy. Simulation and semi-physical experiments show that the algorithm can realize the smooth motion control of the boom and can effectively realize the obstacle avoidance of multiple obstacles in the complex environment.